POLITIK HUKUM: RELASI ANTARA HUKUM DAN BUDAYA SERTA KEMANUSIAAN - Andrian, Dicky; Bahri, Andi Syamsul (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This study explores the legal politics underlying the interplay between law, culture, and humanity. Legal politics serves as a framework for understanding how legal systems are influenced by cultural norms, values, and humanistic considerations within society. The research highlights the dynamic and reciprocal relationship between law and culture, where cultural practices shape legal frameworks, and laws, in turn, impact societal behavior. Furthermore, the study emphasizes the role of humanity in ensuring that legal formulations uphold justice, fairness, and human dignity. It critically examines the challenges of integrating these dimensions in diverse legal traditions, especially in pluralistic societies. By employing an interdisciplinary approach, this research provides a deeper understanding of the philosophical and practical implications of aligning legal frameworks with cultural and humanistic values. The findings underscore the importance of fostering synergy between law, culture, and humanity to create more inclusive and context-sensitive legal systems.